Intelligent Cloud Computing and Automation Using Enterprise Power Platforms - Muppaneni, ajarshi Krishna (International Journal of AI, BigData, Computational and Management Studies, 2026)
Intelligent cloud computing has become a critical base for the ongoing digital transformation all over the world, which helps businesses make the most of scalable infrastructure, advanced analytics, and artificial intelligence to gain higher productivity and better decision-making. This paper investigates the impact of intelligent cloud computing when it is integrated with enterprise power platforms such as Microsoft Power Platform as well as other low-code/no-code automation tools on business agility and operational performance. The power platforms are the toolkits that the enterprises use to uplift the capabilities of not only the technical but also the non-technical employees who can create, automate and optimize workflows, applications and data-driven processes without programming skills thus, lessening the reliance on the traditional software development lifecycles. The main point of the research into the combination of intelligent cloud services with enterprise power platforms aimed at investigating the operational streamlining, productivity improvement and innovation support across the different organizational functionalities as well as business aspects providing cost-saving, scalability, and enhanced collaboration. The author presented a mixed-method research model that integrates the literature review, analysis of enterprise real cases, and qualitative data obtained from interviews with companies that have adopted cloud-based automation solutions. The research activities revolve around the evaluation of performance improvement, implementation difficulty, and level of user acceptance before and after power platforms’ deployment. The main conclusions are that when intelligent cloud computing is integrated with the low-code/no-code platforms, it is possible to develop applications rapidly, have business processes be more flexible, and exploit the organizational data to a greater extent. At the same time, the paper points out that the platforms make it possible for citizen developers to innovate, keeping standards of governance and security in place. The expected outcome of this research is that the enterprises that will have adopted intelligent cloud-powered automations will be able to achieve the quality of digital growth, operational area which is a stronghold, and sustainability of the competitive edge in the business world that keeps getting more and more ​‍​‌‍​‍‌volatile.